An Effective Security Scheme for Attacks on Sample Value Messages in IEC 61850 Automated Substations - S. M. Suhail Hussain; Mohd Asim Aftab; Shaik Mullapathi Farooq; Ikbal Ali; Taha Selim Ustun; Charalambos Konstantinou (IEEE Open Access Journal of Power and Energy, 2023)
The trend of transforming substations into smart automated facilities has led to their swift digitalization and automation. To facilitate data exchange among equipment within these substations, the IEC 61850 standard has become the predominant standard. However, this standardization has inadvertently made these substations more susceptible to cyberattacks, which is a significant concern given the confidential information that is transmitted. As a result, cybersecurity in substations is becoming an increasingly critical topic. IEC 62351 standard provides guidelines and considerations for securing the IEC 61850 messages to mitigate their vulnerabilities. While securing Generic Object-Oriented Substation Event (GOOSE) messages has received considerable attention in literature, the same level of scrutiny has not been applied to Sampled Value (SV) messages despite their susceptibility to cyberattacks and similar frame format. This paper presents the impact of replay and masquerade attacks on SV messages. It also develops a scheme for securing SV messages against these attacks. Due to high sampling rate and time critical nature of SV messages, the time complexity of security scheme is critical for its applicability to SV messages. Hence, in this work, SV emulators have been developed in order to send these modified secure SV messages and investigate their timing performance. The results show that the proposed scheme can mitigate replay and masquerade attacks on SV messages while providing the necessary high sampling rate and stringent timing requirements.